Metabolic Reprogramming in Cancer Cells: Emerging Molecular Mechanisms and Novel Therapeutic Approaches (2022)
The constant changes in cancer cell bioenergetics are widely known as metabolic reprogramming. Reprogramming is a process mediated by multiple factors, including oncogenes, growth factors, hypoxia-induced factors, and the loss of suppressor gene function, which support malignant transformation and tumor development in addition to cell heterogeneity. Consequently, this hallmark promotes resistance to conventional anti-tumor therapies by adapting to the drastic changes in the nutrient microenvironment that these therapies entail. Therefore, it represents a revolutionary landscape during cancer progression that could be useful for developing new and improved therapeutic strategies targeting alterations in cancer cell metabolism, such as the deregulated mTOR and PI3K pathways. Understanding the complex interactions of the underlying mechanisms of metabolic reprogramming during cancer initiation and progression is an active study field. Recently, novel approaches are being used to effectively battle and eliminate malignant cells. These include biguanides, mTOR inhibitors, glutaminase inhibition, and ion channels as drug targets. This review aims to provide a general overview of metabolic reprogramming, summarise recent progress in this field, and emphasize its use as an effective therapeutic target against cancer.